A Kind of Quaternary Sequences of Period 2pmqn and Their Linear Complexity - Qiuyan Wang; Chenhuang Wu; Minghui Yang; Yang Yan (Complexity)
Sequences with high linear complexity have wide applications in cryptography. In this paper, a new class of quaternary sequences over F4 with period 2pmqn is constructed using generalized cyclotomic classes. Results show that the linear complexity of these sequences attains the maximum.